2015
DOI: 10.1007/s10995-015-1765-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Early and Late Gestational Weight Gain with Infant Birth Size

Abstract: Objectives Associations of gestational weight gain (GWG) during specific periods of pregnancy with infant birth size have been inconsistent. Infant sex-specific differences in these associations are unknown. Methods Information on GWG (kg) (total, early [<20 weeks gestation], and late [ ≥20 weeks gestation]) and indices of infant birth size including birthweight (BW), ponderal index (PI), crown-heel length (CHL), and head circumference (HC) was collected from 3,621 pregnant women. We calculated adjusted mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…These results are in contrast with our findings showing that GWG was strongly related to birth length and LAZ and with those results reported by Gondwe et al (2018) showing that average weekly weight gain was positively associated with birthweight and LAZ. However, in another U.S. study of 3,601 women (Wander et al, 2015), a 1-kg increase in total GWG was associated with a +0.04-cm difference in HC, a value that it is virtually identical to the one observed in our cohort. Gondwe et al also found that average b Any level of food insecurity by the Household Food Insecurity Access Scale (Coates et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in contrast with our findings showing that GWG was strongly related to birth length and LAZ and with those results reported by Gondwe et al (2018) showing that average weekly weight gain was positively associated with birthweight and LAZ. However, in another U.S. study of 3,601 women (Wander et al, 2015), a 1-kg increase in total GWG was associated with a +0.04-cm difference in HC, a value that it is virtually identical to the one observed in our cohort. Gondwe et al also found that average b Any level of food insecurity by the Household Food Insecurity Access Scale (Coates et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Only a few studies have examined the relationship between GWG and other anthropometric birth outcomes such as LAZ (Dahly et al, ; Diesel et al, ), HCZ (Wander et al, ), and BMIZ (Diesel et al, ). In Ireland, birth length did not differ significantly between infants of mothers with excessive GWG and those of mothers with inadequate or healthy GWG (Dahly et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to later infant and childhood weight or BMI outcomes, we did not find any associations with total or trimester-specific GWG, neither within nor between twin pairs. Our results confirm previous research which found that both total and trimester-specific GWG were significantly associated with offspring BW in unrelated individuals (comparable to our between-pair effects; Abrams & Selvin, 1995;Margerison-Zilko et al, 2012;Starling et al, 2015;Wander et al, 2015), although some studies found that the association with offspring BW was limited to early and/or mid-pregnancy (Abrams & Selvin, 1995;Brown et al, 2002;Margerison-Zilko et al, 2012;Sekiya et al, 2007;Starling et al, 2015;Wander et al, 2015). Once controlling for shared genes and environment in the within-pair model, we found an effect of total GWG on offspring BW, which is in line with earlier studies (using a similar study design with siblingpairs; Berglind et al, 2014;Lawlor et al, 2011;Ludwig & Currie, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This association persisted at 6 and 12 months following adjustment for gestational age, labour and birth size (Table ). Two groups that represented either high (>1 SD above the mean) or low (>1 SD below the mean) birth size categories were generated . A low birth size was associated with slightly lower nTreg proportion at birth and 6 months of age (Figure B, Table ).…”
Section: Resultsmentioning
confidence: 99%